2021
DOI: 10.1186/s12888-021-03369-x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal influence of COVID-19-related stress on sexual compulsivity symptoms in Chinese undergraduates

Abstract: Background The coping theory shows that stressful life events are associated with individuals’ psychology/behaviors; meanwhile, the coronavirus disease of 2019 (COVID-19) pandemic is known to have impacted individuals’ physical and mental health. Prior studies revealed that undergraduates have many sexual behavior and emotion disorders, which may be impacted during an isolation period, such as the one brought by COVID-19. However, few studies have explored the longitudinal associations between … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
3
5
0
Order By: Relevance
“…As expected, the current results indicate an association between psychological distress and SC during the pandemicrelated contact restrictions. In the context of the COVID-19 pandemic, our findings are comparable to the findings of Deng et al (2021), where psychological distress predicted sexual compulsivity. During the initial contact restrictions, men and women reported higher SC, compared to before the restrictions.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…As expected, the current results indicate an association between psychological distress and SC during the pandemicrelated contact restrictions. In the context of the COVID-19 pandemic, our findings are comparable to the findings of Deng et al (2021), where psychological distress predicted sexual compulsivity. During the initial contact restrictions, men and women reported higher SC, compared to before the restrictions.…”
Section: Discussionsupporting
confidence: 79%
“…There is initial evidence that pandemic-related stress might specifically affect SC. In a study of university students, Deng, Li, Wang, and Teng (2021) examined sexual compulsivity in relation to COVID-19 related stress. At the first point in time (February 2020), COVID-19 related stress was correlated positively with psychological distress (depression and anxiety), but correlated negatively with symptoms of sexual compulsivity.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al ( 24 ) studied the mental health and emotion regulation experience of Chinese nursing undergraduates during covid-19, which was helpful for direct psychological intervention during the pandemic. Deng et al ( 25 ) showed that the greater the COVID-19 related stress, the higher the sexual compulsivity, and the longer the duration of undergraduates' anxiety. Rahimi and Vallerand ( 26 ) studied the role of academic enthusiasm and emotion in procrastination.…”
Section: Related Workmentioning
confidence: 99%
“…However, longitudinal studies from Canada and Hungary have found that CSB symptoms did not change (Bőthe et al, 2022 ) or increased very slightly (Koós et al, 2022 ) during COVID. Another longitudinal study of Chinese college students found that COVID-related stress in February 2020 predicted CSB symptoms in June 2020, and that this effect was mediated by increases in anxiety (Deng et al, 2021 ). While these studies provide limited evidence for an increase in CSB during COVID, they did not investigate how COVID impacted individuals with CSB.…”
Section: Introductionmentioning
confidence: 99%